Training and Assistance in Production of Industrial-Scale Bioslurry Compost Fertilizer to Overcome Fertilizer Scarcity in Puntukdoro Village, Plaosan, Magetan - Pujiati Pujiati; Nurul Kusuma Dewi; Dimas Setiawan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Through the Partner Village Development program, the Training and Assistance Program for Bioslurry Compost Fertilizer Production aims to empower farmer groups (Mulyo Sejati) and livestock groups (Maju Bersama) in Puntukdoro village, Magetan Regency (PPDM). This activity aims to make use of bioslurry waste (available at nearly 200 liters per day) and agricultural and livestock waste, which is abundant in industrially produced Bioslurry compost. The method used in this community empowerment activity is the ABCD (Asset-Based Community Development) approach. From April to December 2021, this activity lasted for eight months. This activity resulted in a map of partner assets, increased partner knowledge of using bioslurry waste, agricultural waste, and livestock (with a 75 percent understanding rate), and increased partner income through profit from production and commercialization. The total revenue generated by partners in a single production cycle is 7.5 million dollars